Pulmonary Actinomyces graevenitzii Infection: Case Report and Review of the Literature - Yuan, Yuan; Hou, Ziliang; Peng, Dan; Xing, Zhenchuan; Wang, Jinxiang; Zhang, Shuai (Frontiers in Medicine, 2022)
Background Pulmonary actinomycosis (PA), a chronic indolent infection, is a diagnostic challenge. Actinomyces graevenitzii is a relatively rare Actinomyces species isolated from various clinical samples. Case Presentation A 47-year-old patient presented with a 3-month history of mucopurulent expectoration and dyspnea and a 3-day history of fever up to 39.0°C. He had dental caries and a history of alcoholism. Computed tomography (CT) images of the chest revealed a consolidation shadow in the right upper and middle lobes, with necrosis containing foci of air. Actinomyces graevenitzii was isolated from bronchoalveolar lavage fluid (BALF) culture and was identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. He received treatment with intravenous piperacillin-sulbactam for 10 days and oral amoxicillin-clavulanate for 7 months. His clinical condition had considerably improved. The consolidation shadow was gradually absorbed. Conclusion Early diagnosis and treatment of pulmonary actinomycosis are crucial. Bronchoscopy plays a key role in the diagnostic process, and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) is an accurate tool for Actinomyces identification.